The BASES expert statement on trainability during childhood and adolescence - McNarry, M.; Barker, A.; Lloyd, R. S.; Buchheit, M.; Williams, C.; Oliver, J. (2014)
The trainability of children and adolescents remains an important, but contentious, issue in pediatric exercise science. In particular, it has been suggested that the periods of naturally occurring accelerated adaptation during puberty reflect `golden periods` or `windows of opportunity` where the effects of training are especially pronounced. The `trigger hypothesis` or maturational threshold are prominent examples of this theory and dictate that training-induced gains during childhood and adolescence will be either minimal or not apparent until the trigger provided by the onset of puberty is reached (Katch, 1983). It has been hypothesised that changes in the hormonal milieu, and other growth factors, associated with puberty provides a period of accelerated adaptation and trainability